The Effectiveness of the Muhadatsah Method in Improving the Maharah Kalam of Students at MTs Al-Ishlah Tanjung Jabung Timur - Khairul Fajri; M. Syukron Maksum (Edumaspul: Jurnal Pendidikan, 2026)
Abstract This study aims to analyze the effectiveness of the muhadatsah method in improving students' speaking skills (maharah kalam) in Arabic learning at MTs Al-Ishlah Tanjung Jabung Timur. The background of this study is based on the low Arabic speaking ability of students caused by the dominance of conventional learning methods oriented toward grammar memorization and translation. This research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The population consisted of all eighth-grade students of MTs Al-Ishlah, with a sample of 60 students divided into experimental and control classes. Data collection techniques included oral tests, observation, documentation, and supporting interviews. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using the t-test. The results showed that the average posttest score of the experimental class was 82.4, higher than the control class score of 71.6. The t-test result showed a significance value of 0.000 < 0.05, indicating that the muhadatsah method significantly affected students' speaking skill improvement. The novelty of this study lies in the implementation of context-based muhadatsah using students' daily life situations in rural madrasah settings, which has not been widely discussed in previous studies. This study recommends the systematic use of the muhadatsah method in Arabic language learning at the junior Islamic school level. Abstrak Penelitian ini bertujuan untuk menganalisis efektivitas metode muhadatsah dalam meningkatkan maharah kalam siswa pada pembelajaran Bahasa Arab di MTs Al-Ishlah Tanjung Jabung Timur. Latar belakang penelitian ini didasarkan pada rendahnya kemampuan berbicara Bahasa Arab siswa yang disebabkan oleh dominannya metode pembelajaran konvensional yang berorientasi pada hafalan kaidah dan penerjemahan. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi experiment melalui model pretest-posttest control group design. Populasi penelitian adalah seluruh siswa kelas VIII MTs Al-Ishlah, dengan sampel penelitian sebanyak 60 siswa yang dibagi ke dalam kelas eksperimen dan kelas kontrol. Teknik pengumpulan data menggunakan tes lisan, observasi, dokumentasi, dan wawancara pendukung. Analisis data dilakukan melalui uji normalitas, uji homogenitas, dan uji hipotesis menggunakan uji-t. Hasil penelitian menunjukkan bahwa nilai rata-rata posttest kelas eksperimen sebesar 82,4 lebih tinggi dibandingkan kelas kontrol sebesar 71,6. Hasil uji-t menunjukkan nilai signifikansi 0,000 < 0,05 yang berarti metode muhadatsah berpengaruh signifikan terhadap peningkatan maharah kalam siswa. Novelty penelitian ini terletak pada penerapan muhadatsah berbasis situasi kontekstual kehidupan sehari-hari siswa madrasah pedesaan yang belum banyak dikaji dalam penelitian sebelumnya. Penelitian ini merekomendasikan penggunaan metode muhadatsah secara sistematis dalam pembelajaran Bahasa Arab tingkat madrasah tsanawiyah.